The role of vocabulary depth in deaf students’ reading comprehension: a systematic review - Paniagua-Martín, Diego; Calvo Álvarez, María Isabel; Gonz´´alez Santamaría, Virginia (Revista de Investigación en Logopedia, 2022)
Different studies in the field of reading comprehension indicate that the oral vocabulary of a language, defined by two variables, breadth and depth, is one of the factors that most contributes to this skill in typical readers; being depth, related to the extension of the semantic representations underlying the concepts, more influential than breadth, which refers to the number of words that a person is able to recognise. Previous studies have shown the difficulties that deaf students have in making associations between words, in establishing relationships between meanings or in the use of synonyms, all of them derived, mainly, from the primary linguistic deficit they present. The aim of this study was twofold: on the one hand, to analyse the results of those studies that evaluate the role of vocabulary depth in the reading comprehension of deaf students and, on the other hand, to demonstrate the influence of vocabulary depth on this skill. A literature search was carried out in the main databases (2010 - 2021). In the initial search 373 articles were identified and, once the inclusion criteria were applied, 8 were those that met the previously defined objectives. The results showed that the recognition of deep vocabulary in research related to the reading development of deaf students could lead to a better understanding of its role in the skills involved in this process. Therefore, it is necessary to delve theoretically into its treatment and its implications for educational practice with deaf students.